IMPLEMENTATION OF THE PANCASILA STUDENT PROFILE STRENGTHENING PROJECT (P5) ON THE THEME OF SUSTAINABLE LIFESTYLE THROUGH ECOBRICKS FOR ELEMENTARY SCHOOL STUDENTS - Ariyanti, Fanny Putri; Maruti, Endang Sri; Rulviana, Vivi (Universitas Muhammadiyah Mataram, 2025)
Abstrak : Penelitian ini bertujuan untuk.menggambarkan pelaksanaan Projek Penguatan Profil Pelajar Pancasila (P5). Penelitian ini menggunakan metode kualitatif deskriptif. Subjek,penelitian terdiri dari guru kelas 4 dan siswa kelas 4 SDN Ringinagung, Magetan. Teknik pengumpulan.data yang digunakan meliputi wawancara, angket, dan dokumentasi. Instrumen penelitian berupa pedoman wawancara, lembar angket, dan lembar dokumentasi. Analisis data dilakukan dengan menggunakan model Miles and Huberman, yang meliputi tahap pengumpulan.data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa implementasi proyek penguatan profil pelajar Pancasila (P5) dengan tema gaya hidup berkelanjutan melalui ecobrik pada siswa kelas 4 SD melibatkan tahapan perencanaan, pelaksanaan, dan evaluasi. Guru menggunakan modul atau RPP yang disesuaikan dengan tema gaya hidup berkelanjutan dan menganalisis kebutuhan siswa. Tema ini mengajarkan pengelolaan sampah plastik, dengan memanfaatkan sampah plastik yang dapat diubah menjadi ecobrik sebagai produk.Abstract: This research aims to describe the implementation of the project of strengthening the profile of Pancasila students (P5). This research uses descriptive qualitative methods. The research subjects consisted of grade 4 teachers and grade 4 students at SDN Ringinagung, Magetan. Data collection techniques used include interviews, questionnaires and documentation. The research instruments are in the form of interview guides, questionnaire sheets, and documentation sheets. Data analysis was carried out using the Miles and Huberman model, which includes the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the research show that the implementation of the project to strengthen the profile of Pancasila students (P5) on the theme of sustainable lifestyles through ecobricks for grade 4 students at SDN Ringinagung is very good for directly understanding concepts such as waste management, skills, problem solving, and developing student character. which is contained in strengthening the profile of Pancasila students. On the theme of a sustainable lifestyle, it teaches students how to manage plastic waste. By using plastic waste, it can be used as eco-brik which will be made into a product.